Airway Consideration in Maxillofacial Trauma. Issue 1 (December 2022) - Singh, Pallav; Mishra, Prabhat; Tiwari, Tanmay; Singh, Gyan Prakash
Management of airway is the most important concern in critically injured patient with life-threatening injuries for an anesthesiologist as well as primary caregiver as it may distort airway anatomy as well as destabilize the cervical spine. These patients are potentially difficult candidates for mask ventilation and endotracheal intubation. Additionally, these patients are prone to regurgitation as they may have full stomach condition. The requirement of maxillofacial surgery is free access to the oral cavity; thus, securing alternate methods to maintain a safe airway is the primary priority. To improve the clinical outcome of these patients, there should be mutual cooperation between the anesthesiologist, maxillofacial surgeon, and ENT surgeon (for emergency tracheostomy, if needed). In this review, we are discussing primary management in emergency, relevant anatomy, difficulty in securing patent airway, and possible approach for airway management in maxillofacial trauma patients.